Analisis Gejala Stroke dalam Konteks Praktek Terapi dengan Metode Certainty Factor - Inayah Sabila (Universitas Methodist Indonesia, 2025)
Stroke is a serious medical condition that can lead to permanent disability if not treated properly. Early identification of stroke symptoms is crucial in determining appropriate interventions, including alternative therapies such as foot reflexology massage. This study aims to analyze stroke symptoms within the context of reflexology massage practice using the Certainty Factor (CF) method. This method is applied to measure the confidence level of symptoms based on interviews with massage practitioners who independently provide therapy services. The results indicate that the CF method can provide a probabilistic analysis that aids in therapeutic decision-making. By understanding symptoms more accurately, reflexology massage can serve as a complementary approach in stroke patient care.